TRANSFORMATIONAL LEADERSHIP IN IMPROVING DOCTORS’ PERFORMANCE IN HOSPITALS: A LITERATURE REVIEW - Istahara; Farida Yuliaty (RADJA PUBLIKA, 2025)
Doctors’ performance is a key factor in determining the quality of hospital services. However, various challenges such as heavy workloads, limited resources, and increasing demands for service quality often reduce the effectiveness of medical staff. In this context, transformational leadership is considered a relevant approach to enhance doctors’ motivation, commitment, and performance. This study aims to analyze the role of transformational leadership in improving doctors’ performance in hospitals through a comprehensive literature review. The research method employed is a literature review by examining various articles, books, and research reports related to transformational leadership and doctors’ performance in hospitals. The analysis was conducted descriptively and critically to identify the relationship between theory and practice in the field, as well as to formulate implementation strategies suitable for the context of Indonesian hospitals. The findings indicate that transformational leadership, through its four main dimensions inspirational motivation, idealized influence, intellectual stimulation, and individualized consideration is able to enhance work motivation, strengthen organizational commitment, and encourage doctors’ innovation in healthcare services. The application of transformational leadership has also been proven relevant in fostering an adaptive, participatory, and quality-oriented organizational culture.